Variable frequency microwave (VFM) curing for PBGA and FSBGA packages - Chua, Riwis Ian Ping. (2008)
This paper outlines the technology difference between VFM and conventional curing, the benefits of VFM curing and shares some initial experiences with the Plastic Ball Grid Array and ways to improve the VFM process.